Analisis Kritis Money Politics Bahaya terhadap Demokrasi - Hasibuan, Indah Malini; Fatimah, Siti; Alfarisi, Muhammad Adib (Universitas Batanghari Jambi, 2025)
Money politics has become a recurring issue and has become widespread in society. Money politics can take the form of cash donations and direct assistance, such as the distribution of basic necessities or souvenirs such as t-shirts or headscarves, commonly encountered during compaigns or before elections. The objects of money politics are generally target at lower-middle class citizens. This research aims to build a theoretical and conceptual understanding of money politics and its dangers to democracy. This study uses normative approach through legislation and relevant literature. The result show that money politics has become ingrained in society due to the lack of religious values held by the public and officials, as well as weak oversight of elections organizers. Money politics poses a real threat to democracy and can become a bridge to the emergence of corruption. Therefore serious enforcement of regulations prohibiting money politics is necessary, while still adhering to the values contained in Pancasila, while Indonesian law is fundamentally sound, the legal image has been tarnished by the behavior of unprofessional and irresponsible individuals.